PENGARUH STRES AKUT TERHADAP KADAR GULA DARAH MENCIT (Mus Musculus) DENGAN PERLAKUAN EKSTRAK ETANOL ALGA COKELAT (Sargassum sp.) - Christy Sahetapy; Indrawanti Kusadhiani; Yuniasih M. J. Taihuttu; Jansye C. Penturi; Johan B. Bension; Vina Z. Latuconsina (Fakultas Kedokteran Universitas Pattimura, 2021)
Stress is a non-specific response in the body to conditions or conditions that occur as a result of exposure to stressors. High stress usually has a negative impact on the body, one of which is increasing blood sugar levels. Brown algae is one of the traditional marine plants and contains secondary metabolite compounds such as alkaloids, flavonoids, and steroids which are antidepressants so that they can prevent the increase in blood sugar levels. This study aims to determine the effect of acute stress on blood sugar levels of mice by giving ethanol extract of brown algae. This research is a true experimental research design with pre test and post test control group design. 30 mice were divided into normal control (KN), negative control (K-), positive control (K +) groups, ethanol extract of brown algae with a concentration of 2.5% (P1) and 5% (P2). The study was started by measuring the initial blood sugar levels in all groups, then groups K-, K +, P1, and P2 were given stress treatment with the FST method for 6 minutes for 7 days. Group K + was given alprazolam at a dose of 0.2 ml at 1 hour before treatment, while P1 and P2 were given brown algae at 30 minutes before treatment. After the treatment, it was followed by measurement of the final blood sugar level. The data from the observations were analyzed using the dependent T-test with a confidence level of 95%. The results showed that the post-test blood sugar levels in the P1 and P2 groups experienced an increase, but the increase was not significant. The results also showed that the significance values (2-tailed) in the P1 and P2 groups were 0.772 and 0.392 (sig> 0.05), meaning that it could be concluded that there was no effect of giving ethanol extract of brown algae on the prevention of increasing blood sugar levels after acute stress.